Types of Hotel Services - Toychievna, Alieva Makhbuba; qizi, Odilova Sitora Ibrohimbek (European Journal of Life Safety and Stability (2660-9630), 2022)
Hotels offer different types of services which have different impacts on the users’ satisfaction and have an influence in various extents on decision making, when it comes to the selection of hotels. As a part of research, empirical analysis based on the importance of different services which hotels provide, was conducted. The idea of research is to determine the importance of different types of services for users. The survey was conducted on a sample of 850 respondents in Serbia. The study used AHP methodology which is used in the decisionmaking process analysis and is suitable for studies defining the rank of relevance of individual elements. The obtained results presented in the study provide information such as, what services offered by hotels have the greatest importance for users. Based on the obtained results in empirical research, and by applying cluster analysis, two different segments of hotel guests are identified based on the preferred services. Segments are statistically different and can represent various targets in the hotel business policy.